ON THE POSSIBLE OCCURRENCE OF 'ARCHAEOMAGNETIC JERKS' IN THE GEOMAGNETIC FIELD OVER THE PAST THREE MILLENNIA - Gallet Y.; Genevey A.; Courtillot V. (My University, 2003)
Archaeomagnetism can provide a high-resolution full-vector description of the Earth’s magnetic field for the past several thousand years. We analyse the bulk of archaeomagnetic data (both direction and intensity) obtained recently in Western Europe and the Eastern Mediterranean covering the past three millennia. We demonstrate a remarkable coincidence between sharp cusps in geomagnetic field direction and intensity maxima (two clear ones at ∼AD 200 and 1400; two presently less well constrained at ∼800 BC and AD 800). These sharp changes may constitute a new feature of geomagnetic secular variation (‘archaeomagnetic jerks’) with time characteristics intermediate between ‘geomagnetic jerks’ and ‘magnetic excursions’.